Effect of Individual Skills and Performance on Humanitarian Organisations: A Structural Equation Model - Shanaka Rajakaruna; Alge Wattage Wijeratne; Tim Mann; Chen Yan (Logistics, 2017)
The significance of Humanitarian Logistics (HL) skills as basic requirements for employment and career development within the HL field has been demonstrated in previous research by the authors. This research showed a strong relationship between recognised HL skills, individual performance and the HL supply chain. With the increasing number of humanitarian disasters globally, it is essential to determine the correlation between individual performance and humanitarian organisational performance. As with previous research, this paper focuses on HL in the Sri Lankan context. Some limited research has already been undertaken on the subject. However, there were a number of major issues identified during this early research that need to be addressed regarding the effective and efficient operation of humanitarian supply chains. These issues include selecting the right personnel for the job, assessing their performance and building and maintaining measurement indicators to evaluate the performance of the humanitarian organisations. A conceptual model based on a Structural Equation Analysis was deduced from an extensive literature survey and was employed to answer these three interconnected issues. The resultant Structural Equation Model (SEM) was used to analyse the conceptual framework with data being gathered from HL practitioners across Sri Lanka by questionnaire. The existence of a relationship between individual skills and HL performance has been demonstrated previously, but not all skills contribute to individual or organisational performance. This research helps prove earlier theories by other researchers regarding the significance of specific skills for performance. The paper also suggests possible areas of future research.